The Influence of Incubator and Accelerator Participation on Nanotechnology Venture Success - Woolley, Jennifer L.; MacGregor, Nydia (Entrepreneurship Theory and Practice, 2022)
This study investigates how venture development programs such as private incubators, university incubators, and accelerators influence the success of participating nanotechnology startups. With the recent growth in such programs, empirical work is needed to compare their impact on participants across programs and with nonparticipants. Using data on firm bankruptcies, liquidation, government grants, and venture capital, we find benefits, but the influence of each venture development program varies greatly. We further investigate the influence of program services and resources to clarify program heterogeneity beyond existing typologies. The results clarify the role of these programs and ecosystem intermediaries.